AKUNTANSI MASJID BERDASARKAN ISAK NO. 35 - Ririn Rumiaty; Nawirah (Jurnal Ilmiah Akuntansi Peradaban, 2022)
The purpose of this study is to determine whether the financial statements that have been presented by Takmir for the construction of the Agung Jami' Mosque of Malang are in accordance with accounting standards for non-profit oriented entities, namely ISAK No. 35. This is done because of the importance of mosque accounting as a form of accountability for funds obtained from Donors which has been managed by the Takmir or Mosque Management by presenting financial reports. This type of research is a descriptive qualitative research that aims to understand how the process of preparing financial statements by the Agung Jami’ Mosque of Malang, the Takmir Pembangunan section. This study uses primary data and secondary data. By using triangulation technique as a test of validity. The results of this study indicate that the financial statements of Takmir for the construction of the Agung Jami' Mosque of Malang which have been presented in the January-December 2021 period are not fully appropriate and have not implemented financial accounting standards for entities that have a non-profit orientation, namely ISAK No. 35. Keywords : Implementation, Financial Statements, ISAK 35, Agung Jami' Mosque of Malang